Economic Education from Bălţi celebrated its 20th anniversary. Librarians have edited a new bibliography (Confluenţe Bibliologice, 2025)
The bibliography is a useful information tool for those who intend to document the scientific concerns of Bălţi academics. The bibliography highlights over 800 bibliographical records: monographs, studies, textbooks, teaching materials, articles, master's theses that highlight the valuable contributions of Bălţi economists to the development of national economic education.
Keywords: bibliographies